Prevalence and serotype distribution of Listeria monocytogenes isolated from foods in Montevideo-Uruguay - Braga,Valeria (2017)
ABSTRACT The aim of this work was to study the prevalence of Listeria monocytogenes in foods obtained in retail shops and food industries located in Montevideo-Uruguay, and to identify the serogroups of the obtained isolates. Three-thousand one-hundred and seventy-five food samples (frozen, deli meats, ready-to-eat and cheese) were analyzed. The obtained isolates were serogrouped by multiplex PCR and serotyped by conventional procedure. Genetic comparisons were performed using pulsed-field gel electrophoresis on a sub-set of isolates belonging to the same serotype successively recovered from the same establishment. L. monocytogenes was isolated from 11.2% of samples. The highest prevalence was observed in frozen foods (38%), followed by cheese (10%). 1/2b and 4b were the most frequently identified serotypes. In six of 236 analyzed establishments we successively recovered L. monocytogenes isolates belonging to the same serotype. Most of them corresponded to serotype 1/2b. Pulsed-field gel electrophoresis profiles suggest that at least 33% of L. monocytogenes 1/2b isolates are genetically related and that may remain viable for prolonged periods. The observed prevalence of L. monocytogenes was lower than reported in neighboring countries. Our findings highlight the role that frozen foods may play in the spread of this pathogen, and the relevance of serotypes 1/2b and 4b.